Treatment of Viral-Bacterial Pneumonias in Pregnant Women and Puerperas in the 2009 Seasonal Influenza Period (a multicenter study) - G. P. Plotnikov; D. L. Shukevich; Yu. A. Churlyaev; Ye. F. Malyugin; Ye. I., Tutolmin; A. A. Vorobyev; V. Ye. Shipakov; L. Ye. Shukevich; S. V. Voyevodin; Ye. V. Grigoryev (Общая реаниматология, 2010)
Objective: to analyze the results of treating viral-bacterial pneumonias in pregnant women and puerperas in the 2009 seasonal influenza period. Subjects and methods. Five hundred and seven pregnant women who were admitted to the clinics of three institutions for the diagnosis of pneumonia between October and December of 2009 were examined; of whom 52 subjects were hospitalized to the intensive care units for severe hypoxia and/or sepsis. The general principles of specific and symptomatic therapies, the efficiency of ventilation modes, organ protection methods, and morphological material were analyzed. Results. The total problems of the diagnosis and clinical course of the disease and the specific features of intensive care were identified. There were 2.4% deaths among all the pregnant women admitted for viral infection concurrent with pneumonia or 23.1% in all the patients admitted to the intensive care unit. The autopsy results were analyzed. Conclusion. The severest viral-bacterial pneumonias were noted in the third trimester of pregnancy. The later start of specific antiviral therapy was an independent predictor of death. Continuous veno-venous hemofiltration is inadequately effective in treating acute lung injury, producing a satisfactory organ-saving effect. The standard respiratory maneuvers showed a low effectiveness during mechanical ventilation. Key words: seasonal influenza A/H1N1, pneumonia, pregnancy, respiratory failure, intensive care.